Investigation of a thin‐film quasi‐reference electrode fabricated by combined sputtering‐evaporation approach - Wang, Nan (2020)
This paper presents the development of a thin‐film quasi‐reference electrode (tQRE), which was fabricated by sputtering silver (Ag) on a conducting gold layer. The Ag layer was subsequently covered by silver chloride (AgCl) with the aid of e‐beam evaporation. The functionality of the tQREs as reliable reference electrodes was confirmed by observing the potential response in solutions with various chloride ion concentrations. The influence of solution pH on the potential change of the tQREs was evaluated. In the solution with controlled ionic strength, the tQREs were able to provide stable and consistent potential outputs. Experimental investigation of the electrochemical sensors with integrated tQREs demonstrated potential applicability of the tQREs to be incorporated into miniaturized and disposable lab‐on‐a‐chip sensors for point‐of‐care/in‐situ measurements.